Long-term vaccine efficacy of a 2-dose varicella vaccine in China from 2011 to 2021: A retrospective observational study - Mingming Shu; Dandan Zhang; Rui Ma; Tianchi Yang; Xingqiang Pan (Frontiers Media S.A., 2022)
ObjectiveA 2-dose varicella vaccine immunization strategy has been implemented in many cities in China, but there is few evidence on a long-term evaluation of the efficacy of the 2-dose varicella vaccine from China. This study aims to assess the long-term vaccine efficacy of the two doses varicella vaccine and analysis of its influencing factors.MethodsA retrospective study was carried out in 837,144 children born between 2011 and 2017 in Ningbo, Easten China. The logistic regression was performed to estimate varicella vaccine effectiveness (VE).ResultsThe overall VE of 2 doses of varicella vaccine compared without the vaccine was 90.31% (89.24-91.26%), and the overall incremental VE of 2 doses of varicella vaccine compared to the 1-dose was 64.71% (59.92-68.93%). Moreover, the varicella vaccination age of the second dose and the interval between 2 doses were both associated with VE. The VE compared to that without the vaccine in children vaccinated at <4 years old was 91.22% (95%CI: 90.16-92.17%) which was higher than in children vaccinated at ≥4 years old (VE: 86.79%; 95%CI: 84.52-88.73). And the effectiveness of the vaccine was 93.60% (95%CI: 92.19-94.75%) in children with the interval of the 2 doses ≤ 24 months significantly higher than in children with the interval of ≥36 months (VE: 85.62%, 95%CI: 82.89-87.91%).ConclusionsThis study provides evidence for long-term VE of the 2-dose varicella vaccine and the better age for 2-dose vaccination and the interval between 2 doses of the vaccine in China.